2022
DOI: 10.3233/bmr-210322
|View full text |Cite
|
Sign up to set email alerts
|

Central sensitization and functioning in patients with chronic low back pain: A cross-sectional and longitudinal study

Abstract: BACKGROUND: Central sensitization (CS) is present in a subgroup of patients with chronic low back pain (CLBP). Studies on the relationship between CS and functioning have limited operationalizations of CS and functioning. OBJECTIVE: To determine whether CS was related to functioning in patients with CLBP (cross-sectional); and to determine whether changes in CS were related to changes in functioning (longitudinal). METHODS: An observational prospective cohort study with data collected at baseline and discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, when a subgroup of patients with persistent MSK-D is examined, the presence of signs of CS seems to be present and of marginal importance in giving indications on the course of symptoms, as these will, in any case, only improve to a limited extent. 68,69 Probably, this reason justifies the slightest difference that emerges from this SR in signs of CS found between samples with two persistent MSK-D present at the same time and subjects with only one MSK-D. 44,51…”
Section: Central Sensitization In People With Msk-d and Chronic Comor...mentioning
confidence: 78%
“…On the other hand, when a subgroup of patients with persistent MSK-D is examined, the presence of signs of CS seems to be present and of marginal importance in giving indications on the course of symptoms, as these will, in any case, only improve to a limited extent. 68,69 Probably, this reason justifies the slightest difference that emerges from this SR in signs of CS found between samples with two persistent MSK-D present at the same time and subjects with only one MSK-D. 44,51…”
Section: Central Sensitization In People With Msk-d and Chronic Comor...mentioning
confidence: 78%
“…They all used very short HRV measurement protocols (10 min or less) and found little associations with central sensitization, catastrophizing, fear of movement, and disability. [21][22][23] A previous meta-analysis of HRV studies comparing chronic pain subjects with pain-free controls showed evident differences in HRV measures. 8 The results of this meta-analysis were heavily influenced by studies that included subjects with fibromyalgia, which was not the case in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Only three previous studies have directly assessed the association of PROMs to HRV in CMP subjects. They all used very short HRV measurement protocols (10 min or less) and found little associations with central sensitization, catastrophizing, fear of movement, and disability 21–23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations